THE EFFECTS OF PHALERIA MACROCARPA EXTRACT ON MITOTIC INDEX AND TUMOR MASS PROGRESSION OF EPIDERMOID CARCINOMA IN SWISS MICE: IN VIVO EXPERIMENTAL STUDY IN SWISS MICE TREATED WITH NEOADJUVANT PACLITAXEL AND CISPLATIN: In vivo experimental study in Swiss mice treated with neoadjuvant paclitaxel and cisplatin - VITO MAHENDRA EKASAPUTRA; MUHAMAD THOHAR ARIFIN; DJOKO HANDOJO (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: Polyphenols in Phaleria macrocarpa (mahkota dewa) can inhibit mitogen-activated protein kinase activity in receptor tyrosine kinases pathway. This can be recognized from the decrease of mitotic index as a response to malignant cells and the reduction of tumor development. This study aimed to determine whether P. macrocarpa may decrease the mitotic index and tumor diameter in epidermoid carcinoma. Methods: The experiment was conducted on 18 epidermoid carcinoma induced Swiss mice divided into four groups: Control, Phaleria administered (0.0715 mg [0.36 ml]/day), chemotherapy administered (paclitaxel 175 mg/m2 and cisplatin 50 mg/m2), and combination group. Tumor size diameter was measured before and after treatment in 9 weeks. Mitotic index was measured at the end of the treatment. Results: There were significant differences in the mitotic index and changes in tumor diameter among groups compared with the control group. The most significant growth inhibition and decrease in mitotic index were in group four. There was a significant positive correlation between tumor mitotic index and changes in tumor diameter (r=0.813). Conclusion: P. macrocarpa is able to decrease tumor cells’ mitotic index and inhibit epidermoid carcinoma’s tumor mass progression in Swiss mice.